P1-S1.18 Investigating a cluster of neonatal herpes at a single institution. (10th July 2011) - Desai, N; Schillinger, J; Bratu, S; Eramo, A; Bowers, C; Agrawal, A
Abstract : Background: Neonatal herpes (NH) is a reportable disease in New York City (NYC); annual incidence is ∼12/100 000 live births; rates are highest among young, and Black non-Hispanic women. Over a 6-month period at our institution, we identified four neonates with disseminated NH. We investigated the cluster to rule out a nosocomial cause. Methods: NH incidence was calculated for the institution and demographics of delivering mothers compared to NYC overall. NH cases were characterised with regard to viral type, birth history, syndrome classification, vital status, maternal serum antibody status, and herpes viral isolates were sought. We reviewed electronic medical records to identify staff common to >2 case-mothers or -infants. We interviewed staff about signs/ symptoms of herpes simplex virus (HSV) infection over the last year, or close contact with a family member with HSV. Maternal hospital rooms, infant isolettes, and ventilators were mapped to rule out common use by case-mothers or -infants. As NH cases were identified, protocols were implemented for notifying paediatrics of maternal post partum fever, and for initiating empiric treatment with IV acyclovir for neonates of febrile mothers. Results: The NH incidence rate at our institution (151/100 000 live births) was >10 times NYC incidence. Women delivering at our institution were younger (41% vs 27% NYC-wide aged <25), and more likely to be Black non-Hispanic (85% vs 22% NYC-wide). Details for case-infants are presented in Abstract P1-S1.18 table 1 below. Among three mothers to case-infants with type 2 HSV, two were antibody positive and one was negative, suggesting she may have had recent infection unapparent at delivery. Herpes viral isolates were retained for only 1 of 4 case-infants. The four case-mothers were delivered by four different obstetricians. Among 11 staff common to >1 case-infant, none had any history or symptoms of HSV infection; no equipment was common to the case-infants and no mothers shared a common room. Conclusions: NH surveillance data provided important context for this investigation; incidence at this institution was much greater than expected, but the patient population is at increased risk for NH. Available data do not support a nosocomial cause for this cluster; retention of neonatal herpes viral isolates would have aided this investigation. Early recognition of the cluster by the treating team and prompt involvement of national and state public health agencies helped guide the investigation and establish novel preventive and empirical treatment protocols.